Sperm Functional Status: A Multiparametric Assessment of the Fertilizing Potential of Bovine Sperm - Timea Sarah Odinius; Mathias Siuda; Matthias Lautner; Claus Leiding; Stefan Neuner; Heinrich Bollwein; Eleni Malama (Veterinary Sciences)
Sperm viability is routinely assessed for the quality control of cryopreserved bovine sperm batches but is not usually conclusive regarding their fertilizing potential. In this study, we investigated the fertility predictive value of bull sperm viability in combination with DNA integrity or the functional status of viable sperm. In addition to sperm viability, we flow cytometrically assessed the percentage of sperm with high DNA fragmentation index (%DFI) and the fraction of viable sperm with low intracellular Ca2+ content and functional mitochondria using the Sperm Chromatin Structure Assay and a five-color staining panel in 791 and 733 cryopreserved batches with non-return rate (NRR) records after ≥100 first services, respectively. Using linear mixed-effects models and conditional inference trees, we examined the potential of sperm viability combined with either DNA integrity or the functional status of viable sperm to predict the batch-specific NRR. Batches with a %DFI of ≤6.86% were more likely to have a NRR of >60%, whereas %DFI values of >6.86% were more likely to be associated with a 55–60% or lower NRR. Combining post-thaw viability with the functional status of viable sperm did not reliably predict the NRR of individual batches. Concluding, the incorporation of DNA integrity assessment can considerably improve sperm fertility prognostics.